2022
DOI: 10.3389/fendo.2022.891313
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on OB-OC-MΦ Axis and miR-23a to Explore the Pathogenesis and Treatment Strategy of Osteoporosis

Abstract: Osteoporosis is a bone metabolic disorder characterized by decreased bone density and deteriorated microstructure, which increases the risk of fractures. The imbalance between bone formation and bone resorption results in the occurrence and progression of osteoporosis. Osteoblast-mediated bone formation, osteoclast-mediated bone resorption and macrophage-regulated inflammatory response play a central role in the process of bone remodeling, which together maintain the balance of the osteoblast-osteoclast-macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 141 publications
0
1
0
Order By: Relevance
“…Osteoporosis is a common chronic orthopedic disease, which is mostly found in the elderly or postmenopausal women [1,2]. Most patients are characterized by a decrease in bone density and abnormal microscopic bone structure, which leads to an increase in bone fragility, which leads to an increase in the risk of fracture [3,4]. The dynamic stability of osteoblasts and osteoclasts is an important condition for maintaining the soundness of normal human bones.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a common chronic orthopedic disease, which is mostly found in the elderly or postmenopausal women [1,2]. Most patients are characterized by a decrease in bone density and abnormal microscopic bone structure, which leads to an increase in bone fragility, which leads to an increase in the risk of fracture [3,4]. The dynamic stability of osteoblasts and osteoclasts is an important condition for maintaining the soundness of normal human bones.…”
Section: Introductionmentioning
confidence: 99%
“…discovered that miR-483-5p can increase the progression of osteoporosis following the analysis and comparison of the gene expression profiles of blood and bone tissue samples collected from osteoporotic patients and normal people, the mechanism of which was established as the promotion of osteoclast differentiation [ 82 ]. A number of researchers demonstrated that the high expression of miR-23a exacerbated the pathological damage from osteoporosis by inhibition of osteogenesis, promotion of bone resorption, and inflammatory polarization of macrophages, finally leading to the occurrence and further progression of osteoporosis [ 83 ]. Eric et al .…”
Section: Introductionmentioning
confidence: 99%